Contemporary reinventions of early devices that flicker and rotate : a particular type of animated installation in the quest for an expanded animation experience - Veras, Christine (Nanyang Technological University, 2018)
This thesis focuses on a particular type of animated installation, specifically one that employs reinventions of proto-cinematic devices that flicker and rotate—the thaumatrope, the phenakistoscope, the zoetrope, the praxinoscope, and the flipbook in its mutoscope form—and thereby provide a contemporary creative alternative to the traditional experience of animation on screen. In fact, this particular type of animated installation not only explores and expands upon characteristics introduced in the early optical toys but transforms the old devices into an expanded animation experience empowered by the astonishment and wonder they elicit in their public. In rethinking theories about and/or related to the proto-cinema era and analysis of contemporary artworks, the author provides evidence in this thesis of the important role that these early animation devices played in engendering their contemporary counterpart—as a particular type of animated installation—investigating their connections, similarities, and differences in the quest for an experience that expands and pushes the boundaries of animation. The works of Gregory Barsamian, Peter Hudson, Eric Dyer, Robert Breer, George Griffin, Kumi Yamashita, Toshio Iwai, Ryusuke Ito, Mat Collishaw, David “Meggs” Hooke, the art collective composed of David Lawrey and Jaki Middleton, Paul Cox, William Kentridge, Roberto Freitas, and Milton Marques constitute the case studies of this particular type of animated installation. The research contained in the thesis exposes and explores the renovation and reconfiguration of animation in its proto-cinematic form as the animated installation in a post-cinematic form, enabling, even in its own way facilitating, the reconnection of past and present to help construct new possibilities for the future of the field of animation. Further, the research reflects upon the consequences of the past and considers an alternative path that cinema could have followed in exploring the potential of the optical toys as devices that produce animation independent of a screen. These optical toys based on flicker and rotation not only contributed incrementally to the technological knowledge that led to cinema but today are reanimated as a specific kind of animated installation. The theoretical reflections of the thesis are complemented by practical investigation, specifically the author’s invention of a new optical device, the Silhouette Zoetrope, and exploration of it as a toy, art object, research tool, and potential animated installation. Indeed, the development of and subsequent improvements to this practical investigation propelled forward the theoretical research, and vice versa. The trinity of history, science, and art are at the foundation of this thesis and its fundamental search for a new perspective on the expanding role of animation in the 21st century.